Enzymatic Hydrolysis Of Breadfruit Starch: Case Study With Utilization For Gluconic Acid Production - Betiku, Eriola; Ajala, O. (Ife Journal of Technology, 2010)
Enzymatic hydrolysis of breadfruit starch using alpha amylase and glucoamylase were investigated. The possibility of using the hydrolysate obtained to produce gluconic acid compared to synthetic glucose was also studied. The optimum temperature for hydrolysis was established as 60 and 50oC for liquefaction and saccharification steps, respectively. The pH and calcium ion were observed to be factors that increased the rate of hydrolysis. The optimum conditions yielded Dextrose Equivalent (DE) of 20 for the liquefaction step after 40 min and increased to 90 during saccharification step 60 min later. The hydrolysate produced was used to culture Aspergillus niger at pH of 5.5 for gluconic acid production. The breadfruit hydrolysate medium yielded 97.20 g/l of gluconic acid from 100 g/l of breadfruit hydrolysate while medium with synthetic glucose as carbon source produced 83.52 g/l of gluconic acid after 72 h of fermentation. About 80% of the breadfruit hydrolysate had been consumed within the first 24 h of cultivation while approximately 90% of the synthetic glucose was consumed within the same period. Maximum biomass concentrations observed were 39.42 and 32.32 g/l for breadfruit hydrolysate and with synthetic glucose media, respectively. These results indicated that breadfruit hydrolysate like other carbon sources can be used to substitute synthetic glucose to produce gluconic acid and this can be scaled-up in a pilot plant.